The Association Between Vitamin D and Multiple Sclerosis Risk: 1,25(OH)2D3 Induces Super-Enhancers Bound by VDR - Lu, Ming; McComish, Bennet J.; Burdon, Kathryn P.; Taylor, Bruce V.; Körner, Heinrich (Frontiers in Immunology, 2019)
A super-enhancer (SE) is a cluster of enhancers with a relatively high density of particular chromatin features. SEs typically regulate key genes that can determine cell identity and differentiation. Therefore, identifying SEs and their effects may be critical in predicting key regulatory genes, such as master transcription factor genes or oncogenes. The concept of signal inducible SE has been developed to describe dense stretches of signal terminal transcription factor (TF) binding region, which provide an entry to explore the interaction between environmental factors (Vitamin D) and genetic factor (risk variants) in complex disease (Multiple Sclerosis). As a complex autoimmune disease, the aetiology and progression of MS, the interaction between Vitamin D and MS risk variants is still unclear, and can be explored from the aspect of signal SE. Vitamin D, as an environmental signal, can bind Vitamin D receptor (VDR) in cells and further regulate gene expression via transcription factor VDR. This study explores the association between VDR super-enhancers (VDR SE or VSE) after 1,25(OH)2D3 stimulation and MS risk SNPs. Firstly, we details the characteristics of VSE by classifying them into three patterns according to their combinations of persistent VDR binding and secondary VDR binding by reanalysing public ChIP-seq and RNA-seq data. Secondly, we indicate the genes with VSE regions that are near MS risk SNPs. Furthermore, we found MS risk SNPs are enriched in VSE regions, and we found some MS risk genes with MS risk SNPs that are overlapped with VDR SE for further exploration. In addition, we found that two clusters of genes with VSE2 or VSE3 are enriched in ZMIZ1 positively associated genes that are highly regulated by 1,25(OH)2D3 or highly expressed in THP-1, respectively. It is the first time that VDR super-enhancers are analysed, and we connect the MS risk SNP with Vitamin D downstream VSE regions.